PENGARUH CAR, NPF, FDR, dan BOPO TERHADAP TINGKAT PROFITABILITAS DENGAN VARIABEL KONTROL SIZE Studi Kasus pada PT. Bank Muamalat Indonesia Periode 2010 – 2017 - Hermawan, Dwi; Fitria, Shoimatul (Diponegoro Journal of Management, 2019)
This study aims to determine the effect of financial ratios on the profitability of PT Bank Muamalat Indonesia. The dependent variable in this study is ROA, while the independent variables are CAR, NPF, FDR, and BOPO; and SIZE as a control variable. The population of this study is PT. Bank Muamalat Indonesia, Tbk. The samples taken are quarterly financial statements of PT. Bank Muamalat Indonesia, Tbk for 7 periods, namely the period 2010 - 2017. Data collected was analyzed by descriptive analysis and multiple linear regression analysis using SPSS 25 computer program. Based on the results of the research conducted, it can be concluded that: CAR has no significant positive effect on the profitability of PT Bank Muamalat Indonesia. NPF and BOPO have a negative and significant effect on the profitability of PT Bank Muamalat Indonesia. While FDR has a positive and not significant effect on the profitability of PT Bank Muamalat Indonesia.